Edukasi Gizi Untuk Meningkatkan Kualitas Hidup Balita Stunting di Desa Pandan Sura Kecamatan Sukoharjo - Putri, Nopi Anggista; Fitriana; Sheilla, Putri; Wulandari, Septi; Putriani, Olif Delfia; Rahmawati, Nira; Anggraeni, Egi; Nisrina, Zalfaa; Salwa, Akhla; Hardiana, Erni; Marshanda, Novi (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Based on data from the Indonesian Nutritional Status Survey (SSGI) conducted by the Indonesian Ministry of Health (2022), the prevalence of stunting in Indonesia in 2022 was 21.6%. Stunting is caused by long-term and short-term factors that influence a person's nutritional status, indicating that certain healthy behaviors can influence food consumption and nutrient intake. Objective: The educational activities in this study aim to increase public understanding of nutritional eating patterns to prevent stunting. Method: This study used a descriptive method, a research technique that aims to present the characteristics of a population or phenomenon methodically and factually. The knowledge of mothers of stunted toddlers was investigated. The target of community service for this population focused on mothers experiencing stunting. Results: Based on the results of the pre-test and nutritional evaluation, the average knowledge score increased from 61% to 96.5%. After nutrition education through reading and leaflet distribution, the knowledge of all participants increased. Post-test results showed that all students were in the appropriate category, meaning they understood the material very well and were in the appropriate category with a minimum score of 76%. In short, this study shows the effectiveness of leaflet-based and interactive learning methods in improving nutritional knowledge of mothers of toddlers.